Uncertain lives: Insights into the role of job precariousness in union formation in Italy - Daniele Vignoli; Valentina Tocchioni; Silvana Salvini (Demographic Research, 2016)
Background: Growing economic uncertainty has become an intrinsic characteristic of contemporary globalized societies in which an increasing number of people are moving in and out of jobs that may give little meaning to their lives. Among other things, economic uncertainty may affect union formation practices. Objective: In this study we address the relationship between employment uncertainty and union formation in Italy. The country typifies a unique case-study in light of its familistic organization, but remains largely under-studied in this respect. Methods: We adopt a mixed-method approach. The qualitative analysis - conducted with focus group techniques - provided an in-depth understanding into the mechanisms of how job precariousness may affect individual perceptions and beliefs on union formation in Italy. The quantitative analysis - conducted through event-history techniques - verified how strong these mechanisms are at the population level. Results: The qualitative exploration allows us to advance the hypothesis - new for the Italian setting - that labor market uncertainty favors cohabitation while employment stability facilitates marriage. The subsequent quantitative analysis provided strong support for this hypothesis for the female population. For men, the largest contrast was found between any work and no work. Contribution: Our findings support the idea that in Italy cohabitation - in contrast to marriage - is more compatible with employment uncertainties of today's labor market. These reflections are valid for women and employed men: When faced with uncertain prospects, they seem to prefer cohabitation to marriage in the light of its more uncertain nature. Alternatively, they might decide to postpone marriage until their outlook on life is more optimistic.